Ultra pH‐sensitive detection of total and free prostate‐specific antigen using electrochemical aptasensor based on reduced graphene oxide/gold nanoparticles emphasis on TiO2/carbon quantum dots as a redox probe. Issue 11 (22nd August 2021) - Aayanifard, Zahra; Alebrahim, Talieh; Pourmadadi, Mehrab; Yazdian, Fatemeh; Dinani, Homayoon Soleimani; Rashedi, Hamid; Omidi, Meisam
Abstract: The development of a rapid, sensitive, and straightforward detection method of prostate‐specific antigen (PSA) is indispensable for the early diagnosis of prostate cancer (PCa). This work relates an electrochemical method using functionalized single‐stranded DNA aptamer to diagnose PCa and benign prostate hyperplasia. The sensing platform relies on PSA recognition by aptamer/Au/GO‐nanohybrid‐modified glassy carbon electrode. Besides ferrocyanide TiO2 /carbon quantum dots (CQDs) probe is used to investigate the effect of nanoparticle‐containing electrolyte. Optimization of incubation time of aptamer/Au/GO‐nanohybrid and volume fraction of nafion were done using Design Expert 10 software reporting 42.4 h and 0.095% V/V, respectively. In ferrocyanide medium, PSA detection as low as 3, 2.96, and 0.85 ng mL −1 was achieved with a dynamic range from 0.5 to 7 ng ml −1, in accord with clinical values, using cyclic voltammetry, square wave voltammetry, and electrochemical impedance spectroscopy, respectively. Moreover, this sensor exhibited conspicuous performance in TiO2 /CQDs‐containing medium with different pH values of 5.4 and 8 to distinguish total PSA and free PSA, resulting in very low limit of detections, 0.028, and 0.007 ng ml −1, respectively. The results manifested the proposed system as a forthcoming sensor in a clinical and point of care analysis of PSA.